MECHANICAL PROPERTIES OF WOOD-PLASTIC COMPOSITE MADE FROM PARTICLEBOARD AND MDF WASTES AND POLYETHYLENE (HDPE) WASTES - Majid Chaharmahali (Regional Information Center for Science and Technology (RICeST), 2005)
The possibility of producing wood-plastic panels using melt blend method was studied in this research and mechanical properties of the panels including flexural modulus, flexural strength, screw and nail withdrawal resistance, and impact strength were studied.Wood -Plastic panels were made from high density polyethylene (as resin) and MDF waste and particleboard waste (as natural fiber) at 60, 70 and 80% by weight fiber loading. Density and dimensions of the panels were 1g/cm3and 35*35*1 cm, respectively. Results indicated that the mechanical properties of the composites are strongly affected by the proportion of the wood flour and polymer in the material. Maximum values of flexural modulus of wood plastic panels were found at 70% fiber content in both methods. Flexural strength, screw and nail withdrawal resistance and impact strength of wood plastic composites reduced with the increase in fiber content from 60% to 80%.